1993
DOI: 10.1007/bf01923957
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythmicity is involved in photoperiodic time measurement in the aphidMegoura viciae

Abstract: The photoperiodic clock in the vetch aphid Megoura viciae is generally accepted to be based on a non-circadian mechanism or "hourglass", as no evidence has been found for the involvement of the circadian system in the photoperiodic response. By using a recently-devised protocol which discriminates between single and repeated night length measurement, we demonstrate here that long-night measurement in Megoura is executed in a repetitive way, and thus that its photoperiodic clock is based on a circadian oscillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…For the blowfly, C. vicina, a damping circadian clock also had been suggested from other experiments by Vaz Nunes et al (1990a) in which it was found that DD had the same inductive value as about 5 long-night (LD 8:16) cycles. Vaz Nunes and Hardie (1993) demonstrated with this protocol that the photoperiodic clock in the aphid, M. viciae, is based on a self-sustained or slightly damped circadian oscillator instead of an hourglass as was generally accepted (Lees, 1973;Saunders, 1982b); in this species, n cycles of LD 12:60 or LD 12:36 resulted in the same incidence of ovipara producers as did 3n or 2n cycles of LD 12:12, respectively. Therefore, the Veerman-Vaz Nunes protocol gave a variety of results.…”
Section: Experimental Tests Of Clock Models and Their Use In Guiding mentioning
confidence: 89%
See 3 more Smart Citations
“…For the blowfly, C. vicina, a damping circadian clock also had been suggested from other experiments by Vaz Nunes et al (1990a) in which it was found that DD had the same inductive value as about 5 long-night (LD 8:16) cycles. Vaz Nunes and Hardie (1993) demonstrated with this protocol that the photoperiodic clock in the aphid, M. viciae, is based on a self-sustained or slightly damped circadian oscillator instead of an hourglass as was generally accepted (Lees, 1973;Saunders, 1982b); in this species, n cycles of LD 12:60 or LD 12:36 resulted in the same incidence of ovipara producers as did 3n or 2n cycles of LD 12:12, respectively. Therefore, the Veerman-Vaz Nunes protocol gave a variety of results.…”
Section: Experimental Tests Of Clock Models and Their Use In Guiding mentioning
confidence: 89%
“…More recently, Vaz Nunes and Hardie (1993) found experimental evidence for a circadian clock in M. viciae despite the typical hourglass responses in NandaHamner experiments observed at various temperatures (Lees, 1986). These results show that a negative Nanda-Hamner response does not necessarily mean that the clock is based on a noncircadian (hourglass) mechanism.…”
Section: Important Questions and Problemsmentioning
confidence: 95%
See 2 more Smart Citations
“…Nowadays, it is generally accepted that the circadian oscillator is involved in insect photoperiodism. Even in M. viciae , Vaz Nunez and Hardie (27) proved the involvement of circadian oscillation by a newly devised protocol. However, it is still unclear whether the circadian oscillator is involved in the time measurement itself.…”
Section: Photoperiodic Clockmentioning
confidence: 99%